2010
DOI: 10.1136/hrt.2010.199919
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between temporal sequence of right ventricular deformation and right ventricular performance in patients with corrected tetralogy of Fallot

Abstract: In patients with cToF, RV outlet deformation is delayed, causing a reduction in RV time delay which is significantly related to impairment in RV performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…Fernandes et al 23 did not identify a significant difference in dyssynchrony parameters in children and adolescents with repaired TOF compared with controls. Van der Hulst et al, 24 however, have reported a delay in activation of the RV outlet in repaired pediatric patients with TOF, compared with normal controls. In our work, the TOF case (adverse outcome) group was not found to be significantly more dyssynchronous than the TOF control group, for any of the parameters investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Fernandes et al 23 did not identify a significant difference in dyssynchrony parameters in children and adolescents with repaired TOF compared with controls. Van der Hulst et al, 24 however, have reported a delay in activation of the RV outlet in repaired pediatric patients with TOF, compared with normal controls. In our work, the TOF case (adverse outcome) group was not found to be significantly more dyssynchronous than the TOF control group, for any of the parameters investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Clinical applications of strain imaging to assess systolic and diastolic function in children with a variety of complex conditions (congenital heart disease, cystic fibrosis, sickle-cell anemia, and chronic lung disease) have recently reported measures of global and segmental longitudinal strain and strain rate. (1224). However, the mean values and associated variations of these strain values need to be firmly established before routine clinical adoption of RV strain measurements can be implemented in children (11).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure of the right ventricle (RV) to a regurgitant load may lead to progressive RV dilatation, and has been associated with adverse events such as increased symptoms, arrhythmia and death 2–6. Potential causes of RV dysfunction in adults with repaired TOF include abnormalities of the temporal pattern of RV mechanical activation 7. Although pulmonary valve replacement (PVR) is an effective way of reducing the volume load on the RV, there is no proof from prospective studies that it reduces the risk for adverse outcomes, such as sudden cardiac death, sustained ventricular arrhythmias or heart failure 8–13.…”
Section: Introductionmentioning
confidence: 99%